(untitled) (Research, Society and Development, 2022)
The article focuses on knowing the humanization of care offered to health users, which is essential for quality care. Humanization and quality of care for health users as a whole is a task that must transcend bureaucratic spheres that involve only standardization. The general objective of this work was to demonstrate how the Social Worker can intervene in the context of the main difficulties faced by health users and promote humanization in the health area. As for the methodology, the work includes a literature review, based on an eminently bibliographical research. With the completion of the research, it could be observed that humanization is a fundamental factor for the development of quality care for health users and their families, covering not only pathophysiological problems, but also biopsychosocial problems. And in the context of public health, dissatisfaction on the part of users is often observed. In humanized care, there is a holistic view that encompasses an interpersonal relationship, which includes actions such as listening carefully to users and accessing information relevant to their needs. In this scenario, the role of the Social Worker is highlighted, who, in partnership and integration with other health professionals, can develop a more humanized, welcoming and quality care, also seeking mechanisms for access to health, as provided for in the Health Humanization Policy , and which prescribes that the lines will be reduced and the waiting time with expansion of access to health and welcoming and resolute care.